(untitled) (Research, Society and Development, 2021)
In Santos Beach, southwest coast of Brazil, cleaning operations are intensified during the summer using manual and mechanical techniques, driven mainly by sanitary and aesthetic aspects that neglect basic ecological standards. This study evaluated the abundance, richness, and diversity of dead shells, after spring and neap tides, found in two strips of sandy beaches: the "damp" and the "wet "sectors, where only the former undergoes mechanical cleaning. We collected and counted all fragmented and whole shells, identified each down to the species levels, and measured their weight. We used mixed statistical modeling to evaluate the effect of the sector over the abundance (in weight and number), richness, and Shannon-Wiener diversity (). We found a significantly greater abundance of fragmented shells in the damp sector. Since this is the sector where mechanical cleaning is applied, we understand such a strategy promotes potential harmful impacts over the conchological structure in Santos Beach, requiring mitigatory measures to protect empty shells. Finally, we fathom incorrectly discarded litter is brought from the surrounding mangrove to the beach after the spring tides; thus, integrated cleaning management with the participation of the local population, are also required to reduce the mechanical cleaning and its impacts.